Diagnosis of clinical bovine mastitis by fine needle aspiration followed by staining and scanning electron microscopy in a Prototheca zopfii outbreak - da Costa, E. O.; Ribeiro, Márcio Garcia [UNESP]; Ribeiro, A. R.; Rocha, Noeme Sousa [UNESP]; de Nardi, G. (Kluwer Academic Publ, 2004)
Biopsy by fine needle aspiration together with microbiological examination and scanning electron microscopy were evaluated in diagnosis of clinical bovine mastitis in a Prototheca zopfii outbreak. Fine needle aspiration was performed in 21 mammary quarters from ten Holstein cows presenting clinical mastitis caused by P. zopfii. The algae were previously identified in the microbiological examination of milk collected from these cows. Material aspirated from these 21 mammary glands was submitted to cytological staining (Gram, Giemsa and/or Shor staining). Fine needle aspiration enabled cytological identification of the algae in these 21 mammary glands, from which P. zopfii was isolated in the milk. Simultaneously, five mammary fragments collected by fine needle aspiration from these 21 mammary glands presenting clinical mastitis were also submitted to microbiological examination. P. zopfii was also isolated from these five fragments. Scanning electron microscopy technique also identified three of these five P. zopfii strains isolated from mammary fragments collected by cytological aspiration. These results suggest that fine needle aspiration may be an alternative method for the diagnosis of clinical mastitis.
Keywords: bovine mastitis; Prototheca zopfii; fine needle aspiration; scanning electron microscop